THE ROLE OF CLASSROOM TASKS IN DEDUCTIVE AND INDUCTIVE GRAMMAR INSTRUCTION - Kurbonova Iroda; Orzikulova Mavsuma Mamatkulovna (Ta’lim innovatsiyasi va integratsiyasi, 2026)
The paper examines the role of classroom tasks in the process of the learning of grammar through deductive and inductive approaches to grammar instruction in ESL and EFL contexts. Specifically, it focuses on how different types of the classroom tasks contribute to students’ grammatical development, cognitive engagement and overall language acquisition. Most concepts relate to task structure, the degree of instructional sequencing, and the amount of teacher guidance. Comparing rule-oriented deductive tasks and discovery-oriented inductive tasks on accuracy, fluency, and metalinguistic awareness, the result shows deducing rules has advantages for explicit grammatical knowledge, rapid discovery of rules, and controlled practice, especially among lower skilled learners. Inductive tasks, on the other hand, require exploration, hypothesis generation and deep processing which results in real learning and information retention. Based on the findings, the paper suggests that an integrated task-based approach which combines both deductive and inductive approaches should be adopted to better increase grammar learning. Therefore, the paper concludes by arguing that the appropriate implementation of well-structured classroom tasks is pivotal to maximizing the benefits of grammar instruction, as it meets the needs of different learners and adopts a learner-centered approach as well as promoting explicit and implicit learning